2024
DOI: 10.4093/dmj.2023.0110
|View full text |Cite
|
Sign up to set email alerts
|

Primordial Drivers of Diabetes Heart Disease: Comprehensive Insights into Insulin Resistance

Yajie Fan,
Zhipeng Yan,
Tingting Li
et al.

Abstract: Insulin resistance has been regarded as a hallmark of diabetes heart disease (DHD). Numerous studies have shown that insulin resistance can affect blood circulation and myocardium, which indirectly cause cardiac hypertrophy and ventricular remodeling, participating in the pathogenesis of DHD. Meanwhile, hyperinsulinemia, hyperglycemia, and hyperlipidemia associated with insulin resistance can directly impair the metabolism and function of the heart. Targeting insulin resistance is a potential therapeutic strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 144 publications
0
0
0
Order By: Relevance
“…Insulin resistance (IR) is a common feature observed in individuals with metabolic syndrome and T2DM. It is considered a key indicator of diabetes-related heart disease (DHD) ( 5 ), which encompasses coronary artery disease, autonomic heart disease, and diabetes cardiomyopathy (DCM) ( 6 ). DCM increases mortality in diabetes patients ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance (IR) is a common feature observed in individuals with metabolic syndrome and T2DM. It is considered a key indicator of diabetes-related heart disease (DHD) ( 5 ), which encompasses coronary artery disease, autonomic heart disease, and diabetes cardiomyopathy (DCM) ( 6 ). DCM increases mortality in diabetes patients ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have demonstrated that insulin resistance (IR) can affect blood circulation and the myocardium, myocardial fibrosis, cardiac hypertrophy, and ventricular remodeling. These effects contribute to the development of DHD and may ultimately lead to cardiac diastolic dysfunction and progression to HF ( 5 ).…”
Section: Introductionmentioning
confidence: 99%